Power and Precision Grip in Patients with De Quervain’s Disease - Aqsa Rizwan; Yamna Mazher; Hassan Shahid (Journal Riphah College of Rehabilitation Sciences)
Background: De Quervain's disease, characterized by inflammation of thumb tendons, is a common cause of wrist pain. This study emphasizes the crucial role of power and precision grip in De Quervain's patients, highlighting its significance for medical assessments.